2015
DOI: 10.4314/mejs.v7i1.117234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of botanicals for onion thrips, <i>Thrips tabaci</i> Lindeman, (Thysanoptera: Thripidae) control at Gum Selassa, South Tigray, Ethiopia

Abstract: Field studies were conducted for two consecutive years (2013 and 2014) to determine the effectiveness of different plant extracts and synthetic chemical insecticides for the control of onion thrips (Thrips tabaci) at Adigudom, Southern Tigray, Ethiopia. Two chemical insecticides including dimethoate 40% E.C and Lambda-cyhalothrin (Karate 5 EC), and five botanical extracts obtained from neem (Azadirachta indica A. Juss), Mexican marigold (Tagetus minuta L.), tree tobacco (Nicotiana glauca Graham) and Jimson wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Onions sprayed with spinosad + neem oil had fewer T. tabaci and produced higher yields than onions that were unsprayed, regardless of mulch type or onion cultivar. Previous studies in onion production regions of the United States and Pakistan have shown that biopesticides are effective for reducing T. tabaci densities in onion [ 47 , 57 , 58 , 59 , 60 ]. However, efficacy depends on the biopesticide applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Onions sprayed with spinosad + neem oil had fewer T. tabaci and produced higher yields than onions that were unsprayed, regardless of mulch type or onion cultivar. Previous studies in onion production regions of the United States and Pakistan have shown that biopesticides are effective for reducing T. tabaci densities in onion [ 47 , 57 , 58 , 59 , 60 ]. However, efficacy depends on the biopesticide applied.…”
Section: Discussionmentioning
confidence: 99%
“…Several botanical extracts also have been evaluated for T. tabaci control in onions. Azadirachtin, derived from the neem tree seeds or leaves ( Azadirachta indica Juss), provided moderate reductions in T. tabaci densities in studies conducted in the Pakistan [ 58 , 60 ] and feeding damage in studies conducted in New York, United States [ 48 ], but improvements in yield were inconsistent. In studies conducted in Ethiopia and Pakistan, Fitiwy et al [ 60 ] and Khaliq et al [ 58 ], respectively, reported reductions in thrips densities of 17.2% and >60% using extracts of Datura spp., respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been trials to establish aromatic insecticides from various plant species to control onion thrips at field and greenhouse conditions and the following have been recommended: Artemisia arborescens, Azadirachta indica L., Chrysanthemum cinerariifolium, Datura stramonium, Dodonaea angustifolia L., Dianthus caryophyllus, Melaleuca alternifolia, Nicotiana glauca, Origanum majorana, Ocimum gratissimum, Rosmarinus officinalis, and Tagetes minuta (Fitiwy et al 2015;Omosa et al 2016;Prabhu et al 2011;Shiberu & Negeri 2014;van Tol et al 2007).…”
Section: Ways To Control Onion Thrips Aromatic Plantsmentioning
confidence: 99%